Recovery of a triazole-resistant Aspergillus fumigatus in respiratory specimen of COVID-19 patient in ICU – A case report (2020)
Although invasive pulmonary aspergillosis (IPA) is typically described in immunocompromised host, patient with severe influenzae can develop IPA. Similarly, patients with severe COVID-19 complicated with IPA are increasingly reported. Here, we describe a case of invasive aspergillosis with triazole-resistant A. fumigatus (TR34/L98H mutation) in a 56-year-old patient with COVID-19 in intensive care unit. This report highlights the need to define the available tools for diagnosis of invasive aspergillosis in severe COVID-19 patients.